Current and Potential Pharmacological Targets for Therapeutic Intervention in Head and Neck Squamous Cell Carcinoma - Madhukar , Geet; Subbarao , Naidu (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
Despite significant advancements in the treatment of Head and Neck Squamous Cell Carcinoma (HNSCC), it remains a significant global public health challenge. HNSCC is a complex cancer affecting the upper aero-digestive tract. Current cancer treatment strategies involve using anticancer drugs to target proteins with abnormal expression. Researchers are exploring novel cancer targets based on a better understanding of the molecular mechanisms involved in intracellular processes. Therapeutic options targeting these specific targets, such as Cetuximab, Pembrolizumab, and Nivolumab, are currently available or under development. With advancing knowledge of molecular mechanisms, there is a growing opportunity to identify and exploit new drug targets for HNSCC. Although targeted chemotherapy has shown some success in treating HNSCC, the survival rates and recurrence rates have not improved significantly due to several challenges. These challenges include undesirable reactions to chemotherapy, lack of specificity of drugs, drug resistance, and toxicity to non-cancerous tissues and cells. Researchers have conducted extensive studies to identify effective drug targets for HNSCC treatment. This chapter provides valuable insights into these promising anticancer targets and details the drugs currently under various stages of development. Moreover, it also explores new potential targets that have not been explored in much detail for their impact on HNSCC. We believe that investigating and developing drugs targeting these new potential targets could be beneficial in the treatment of HNSCC.